Landslide susceptibility mapping using GIS approach / Munirah Radin Mohd Mokhtar and Suriani Ngah Abdul Wahab - Mohd Mokhtar, Munirah Radin; Abdul Wahab, Suriani Ngah (2021)
There are many approaches in monitoring landslides, but Close Range Photogrammetry (CRP) provides mapping achieved almost in real-time at a low cost compared with another approach. CRP is a conception technology which is used to acquire 3D spatial information on objects in inaccessible areas. The method concerns camera calibration, which includes a process of the determination of the right parameters of the camera. The information is obtained through accurate assessment and used to create a 3D model which would be used for monitoring technique applications. In this study, calibration of the digital camera was performed using PhotoModeler Pro 5. A good calibration will have many points marked. Field observations of the on-site survey were carried out over a monitoring area in Parit, Seri Iskandar, Perak. The landslide can be detected by the calculation of two different epoch data achieved from the Digital Elevation Model (DEM) generation. The paper focuses on the observation of the studied area based on DEM area and volume generated from the 3D surface analysis.